The Changing Role of School Libraries/Media Resource Libraries in Secondary Schools in Singapore and the Need to Implement Mandatory Standards, 1946-2010: Issues, Challenges and Opportunities / Lim Peng Han - Lim, Peng Han (2011)
The aim of this paper is to study the development and evolution of secondary school libraries into Media Resource Libraries (MRLs) in Singapore after the Second World War and the rationale to have mandatory school library standards. It is an historical survey analysing published data about the linkages of libraries and librarianship, school library standards, education and school reforms in Singapore. It analyses historical and current documents on the roles played by stakeholders like the Library Association of Singapore (LAS) and the Ministry of Education (MOE) in the introduction and development of school library standards. The need for school libraries standards was first discussed when the Malayan Library Group (MLG) organised the first course on librarianship for school teachers in 1955. But there was no follow up. The need for school libraries standards was also mentioned by the LAS in 1962 when a memorandum to the Commission of Enquiry into Education to train teacher librarians and school library standards to be formulated and adopted in schools. However, it was left out in the final report of the Commission published in 1964. The need for school library standards was discussed in a school library seminar for 150 teacher librarians in 1970. The first Recommended minimum standards for secondary school libraries was published two years later by the Standing Committee on Libraries set up by the MOE. But it was not mandatory of schools to adopt the standards. In 1997 the MOE launched its ―Thinking School Learning Nation‖ vision to teach thinking skills. Students were expected to do multidisciplinary project work and to be independent users of information. The MOE began to convert school libraries into Media Resource Libraries (MRLs) with print and non-print materials. However, a survey conducted in 2001 on the roles and competencies of 112 Library Coordinators (LCs) or teacher librarians revealed that they lack the skills and knowledge to management MRLs effectively. This is because subsequent school library standards published in 1983 and 2002 did not require trained and full-time teacher librarians to manage the MRLs. Furthermore, it is essential for the standards to be periodically updated with regards to professional staff, collection development, facilities, Information and Communications Technology (ICT) infrastructure and school library programs. Otherwise MRLs risk to being ―hollow shells still considered on the periphery of core educational requirements‖, and are run by teachers not professionally prepared to do the work. The national standards published in the United States from 1918 to 2008 are well researched and provided substantive guidelines to develop school libraries. Therefore it is essential for the MOE to formulate MRL standards by doing comparative studies of school library standards in other countries. These standards have to be mandatory and fully adopted by the schools. It provide opportunities for stakeholders like the LAS, National Library Board (NLB), the National Institute of Education (NIE) and the Singapore Teachers‘ Union, to collaborate in the formulation these standards and take collective ownership to implement them.